Case report: Abdominal hernia repair using a surgical wire and an autologous omental graft in a Japanese Black calf - Sato, Reiichiro; Kim, Sueun; Okada, Shoichi; Ikedo, Tomonobu; Satoh, Hiroyuki; Steiner, Adrian (Frontiers in Veterinary Science, 2023)
Background: Hernia formation is a well-known abdominal wall disorder in calves and most often occurs in the umbilical region. In addition, it occurs in the abdominal wall outside the umbilical region. It has been reported to involve acquired factors, such as external force to the lower or lateral abdominal wall, trauma, muscle weakness, and, although rare, congenital or hereditary factors. Although there have been reports on the repair of abdominal wall hernias caused by abnormal muscle formation, there have been no reports on the treatment of abdominal wall hernias caused by abnormal vertebral and rib formation in cattle or other ruminants. In this study, for the first time, we describe a case of successful closure of a hernia in the left flank caused by malformation of the vertebrae and ribs. The repair was performed by narrowing the ribs using a surgical wire and covering the defect with a free omental graft. Case presentation: A male Japanese Black calf showed a mild bulge of the left abdominal wall and abnormal morphology of the left ribs immediately after birth. At 3 months of age, computed tomography revealed fusion of the 9th, 10th, and 11th thoracic vertebrae and missing formation of the 10th and 11th left ribs at the thoracic vertebral fusion site. Additionally, a 15.2 × 24.4-cm abdominal hernia had formed in the abdominal wall. During surgery, the ribs forming the hernia were narrowed with a surgical wire, and the hernia was covered with a large autologous free omental graft to prevent intra-abdominal organ prolapse. At the monthly follow-up (11 months after surgery), the calf had developed similarly to other calves of the same age on the farm, and no complications were noted. Conclusions: The current case shows that a combination of rib correction using a surgical wire combined with transplantation of a free autologous greater omentum graft was shown to be a possible treatment option for surgical repair of large abdominal wall hernias caused by rib malformation.